MITIGASI RISIKO DROP SELLING PADA PELAKU UMKM MENGGUNAKAN E-COMMERCE (STUDI KASUS: UMKM KAMPOENG SNACK): MITIGASI RISIKO DROP SELLING PADA PELAKU UMKM MENGGUNAKAN E-COMMERCE (STUDI KASUS: UMKM KAMPOENG SNACK) - Saifuddin Saifuddin; Siti Zulaeha (Universitas Lancang Kuning, 2022)
The rapid growth of UMKM along with the progress of e-commerece makes business competition more intense. UMKM Kampoeng Snack as one of the businesses engaged in the distributor of UMKM products in the village community, as a new player in the world of e-commerce often experience the risk of declining sales. To analyze the existence of such cases, this study was conducted using field research methods with descriptive qualitative approaches. The interview was conducted to Kampoeng Snack managers and the community of UMKM who are members of the Kampoeng Snack UMKM. The risk of declining sales faced by Kampoeng Snack occurs due to several factors based on the lack of interaction between Kampoeng Snack administrators and the community. So that this triggers a delay in human resources of e-commerce which then causes a decrease in sales often occurs. Therefore, the application of risk mitigation becomes an alternative solution to minimize the risks that occur. through the right decisions and steps in accordance with the procedures that have been set.